Influence of Sparkle and Saccades on Tongue Electro-Stimulation-Based Vision Substitution of 2D Vectors - Chekhchoukh, Abdessalem; Glade, Nicolas (Acta biotheoretica, 2012)
Vision substitution by electro-stimulation has been studied since the 60s beginning with P. Bach-y-Rita. Camera pictures or movies encoded in gray levels are displayed using an electro-stimulation display device on the surface of a body part, such as the skin or the tongue. Medical-technical devices have been developed on this principle to compensate for sensory-motor disabilities such as blindness or loss of balance, or to guide specific actions, such as surgery. However, the electrical signals of stationary or moving slowly moving objects, displayed on a Tongue display unit (TDU), are quickly lost due to saturation of receptors undergoing electrostimulation. We propose to add random saccades or sparkle to the displayed visual scene to increase the quality of pattern recognition by the subjects. In the present experimental trimodal study (normal vision, TDU vision substitution, or both), we show that the presence of a moderate sparkle level enhances the perception of the direction of lines drawn on a TDU and reduces the response time.